Which Country is More Effective in Science Teaching? Evidence from PISA 2015 as a Secondary School Assessment Tool - Ilgaz, Gökhan; Eskici, Menekşe; Vural, Levent (Asian Journal of Education and Training, 2019)
The aim of this study is to determine how effectively different countries use educational inputs in the process of science education. The study is in the descriptive model and the data is derived from the PISA 2015 data set, which provides information to countries on secondary education programs. Data from 70 countries, including Turkey, were used in the study. The effectiveness of Turkey in the process of science teaching in secondary education has been compared with other countries and suggestions have been made to increase the effectiveness of secondary education science teaching. The data for this study are grouped into training inputs and training outputs. “Student behaviour hindering learning”, “teacher behaviour hindering learning”, “shortage of educational material”, “shortage of educational staff”, “professional development”, “teachers participation”, “curricular development”, “total number of science teachers at school”, “index science-specific resources (sum)” were defined as the educational inputs. The science achievements of students have been taken into account in determining which countries have more effective management of educational inputs accepted in this study. Secondary scholl level education inputs while nearby countries respectively to use effectively Slovakia (97.30%), Slovenia (91.16%), Brazil (90.50%), Turkey (89.75%), Finland (84.65%), Greece (83.31%), Denmark ( 83.25%), and Czech Republic (80.61%). education outcomes in Turkey is ranked as 20th in science teaching secrets to use it effectively.